Multiple stress memory characteristic of rocks under uniaxial deflection loading: Insights from acoustic emission signals - Chunde Ma; Wenyuan Yang; Zelin Liu; Guanshuang Tan; Junjie Zhang (International Journal of Coal Science & Technology)
Abstract The acoustic emission (AE) method is commonly used to measure in-situ stress, while the Kaiser effect (KE) is usually affected by the stress history and specimen direction. In this study, three types of rocks were tested under uniaxial deflection loading at various deflection angles. Both the KE and the incomplete erasion phenomenon (IEP) were investigated, and the obtained in-situ stress using the AE method was compared with that obtained using the stress relief method. The results demonstrate that both the KE and the IEP exhibit directional independence. The rock type significantly affects the critical angle (θ), with marble showing a higher value (15°) compared to granite (10°) and red sandstone (5°). This is attributed to the initiation and development of interface cracks or crystal interfaces in mineral grains. The similar in-situ stress measured by the AE and stress relief methods suggests that small-angle deflection coring is applicable in engineering. This study provides a reference for in-situ stress measurement using the AE method.